LE CAPACITÀ SOCIO COGNITIVE NEL CANE DOMESTICO (CANIS FAMILIARIS): DIFFERENZE TRA RAZZE ED UN CONFRONTO CON IL LUPO(CANIS LUPUS) - C.A. Passalacqua (Frontiers in Veterinary Science, 2011)
In the past ten years there has been a considerable increase in the number of studies on dogs’ cognitive and communicative abilities. Recent evidence indicates that both genetic factors and life experiences are important in shaping dogs’ socio-cognitive abilities and behaviour in a test situation. An interesting approach to the investigation of the origin of such abilities is the comparison between different dogs’ breeds and with the dogs’ wild ancestor: the wolf. In the present work we used two different test paradigm to investigate genetic (breed-group) and ontogenetic (age) factors influencing the use of human-directed gazing behaviour and the influence of humans on dogs’ performance in a food choice task using either different of equal quantities of food. Following a genetic classification based on recent genome analyses, dogs were allocated to three breed groupings based on their vicinity to the wolf and to each other (primitive, hunting/herding and molossoid group) and were tested at different ages. Furthermore one of the two test, the ‘unsolvable task’ paradigm similar to that used by Miklósi and colleagues (2003), was used to compare dogs and wolves hand raised from humans and socialized with them, to investigate the influence of genetic aspects in the use of human-directed gazing behaviour. In the “unsolvable task” test Breed group differences did emerge strongly in adult dogs and, although less pronounced, also in 4.5-month old subjects, with dogs in the Hunting/Herding group showing significantly more human-directed gazing behaviour than dogs in the other two breed groups, whereas at two months no breed group differences emerged. Also in the social influence test we found the same pattern in adult dogs where Hunting/Herding dogs showed to follow the human choice more than the Molossoid dogs, as opposite to 4-months old dog that neither could discriminate between the two different quantity of food nor followed the humans’ choice. Comparisons between dogs and wolves showed the former gazing and ...